Uma metapsicologia para o agente social: outro entendimento de pessoa para a teoria social de Margaret Archer - Santos, Waldez da Silva (2020)
Instigated by the classic dilemma of the relations between individual and society, this work will focus on them by having the social theory of Margaret S. Archer and the metapsychology of Sigmund Freud to account for each term of the question. From the first, we will extract a definition of society — based on the ideas of Social Structure and Cultural System — that does not confuse it with the individuals that populate it and points out its place in the complex social phenomena.Given the way Archer theorizes, the problem of the relationship between society and the individual will become the problem between society and people. Archer will understand personhood as a set of concerns so important that they can guide people’s action together with reflexivity, i.e., the ability that people have to perceive themselves and the world around them and ponder over the best way to take care of your concerns. In the second, we will seek an understanding of the individual beyond his rational capacities through his drive dynamics. For that, we will go through the various moments of Freud’s psychoanalytic theorizing about the ego — the most appropriate metapsychological agency for social treatment — and the unconscious — whose functioning mechanisms give little value to society. We will go through, with the aid of the drive concept, the different ways in which the two instances in question are theorized: a) that initial one in which sexual drives share the psyche with the instincts of self-preservation, b) the birth of the concept of narcissism that marks the hegemony of sexual drives and, finally, c) the psyche after the death instincts. At the end of this work, we expect to change the notion of person developed by Margaret Archer for one found in Sigmund Freud’s psychoanalytic works. We also expect that this operation will show the benefits that an approximation between the disciplines would bring to them.